Locating the Invariant Faxtor’s Cognitive Ability Test - Adjie, Aryo Bimo; Nasyiah, Fatiya Nurhadi (Journal of Educational, Health and Community Psychology, 2023)
Ensuring consistency in measurements across different groups is a crucial aspect of using intelligence test scores and other psychological assessments fairly. Many believe that having equal factor loadings is enough to establish this consistency in confirmatory factor analysis. This research focused on examining the consistency of the Factor Cognitive Ability Test (FCAT) between genders and age groups. A second-order 4-factor model was applied to a nationally representative sample of 3,850 individuals aged 11 to 53 years. The results revealed complete strict consistency between genders and basic structural consistency among age groups. The FCAT subtests exhibited identical underlying theoretical latent constructs, equivalent relationships among factors and subtests, consistent validity for each first-order factor, and comparable communalities, irrespective of gender. This supports a consistent interpretive approach and meaningful comparisons of FCAT scores between males and females. However, the study also identified variations across age groups, indicating non-consistency and providing evidence that age has an impact on the latent variable differences in FCAT scores.